Efeitos do etil‐2‐cianoacrilato e do butil‐2‐cianoacrilato no processo de consolidação óssea em ratos. Estudo experimental controlado - Palacio, Evandro Pereira [UNESP]; Pereira, Gilberto José Cação [UNESP]; Silvares, Paulo Roberto de Almeida [UNESP]; Di Stasi, Gabriel Guimarães; Staut, Caio de Andrade; Sardenberg, Trajano [UNESP] (Thieme, 2018)
Objective Synthetic adhesives are used by various medical specialties, especially in surgery; however, studies reporting their use in orthopedic practice are scarce. The aim of this study was to compare the results in using ethyl‐2‐cyanoacrylate or butyl‐2‐cyanoacrylate in the treatment of fractures in rats. Methods This was an experimental prospective controlled study in 90 rats, with humerus, femur, and tibia fractures, treated with ethyl‐2‐cyanoacrylate (SB group; n = 45) or butyl‐2‐cyanoacrylate (HA group; n = 45). Biomechanical and histomorphometric analyses were performed at three different moments (60, 120, and 180 days); besides a clinical study performed weekly by measurement of the animals body mass. Results No differences were observed regarding body mass (p = 0.07). In both groups, there were no significant differences regarding maximum load (p = 0.6), yield point strength (p = 0.6), and stiffness coefficient (p = 0.4) of the femurs. The same was observed in tibias for maximum load (p = 0.4), yield point strength (p = 0.7), and stiffness coefficient (p = 0.6). The humerus from both groups had similar bone callus area (p = 0.66). In both groups, there were no statistical differences related to inflammatory cells (p = 0.4), osteoblasts (p = 0.2), and osteoclasts (p = 0.2). Conclusion Ethyl‐2‐cyanoacrylate was more effective than butyl‐2‐cyanoacrylate in the treatment of fractures in rats.
The effects of ethyl‐2‐cyanoacrylate and butyl‐2‐cyanoacrylate in the process of bone healing in rats. A controlled experimental study
Keywords: Cyanoacrylates; Fracture healing; Fractures, bones; Tissue adhesives